LAYANAN BIMBINGAN KELOMPOK DENGAN TEKNIK DISKUSI DALAM MENINGKATKAN KEPERCAYAAN DIRI SISWA SMA KELAS XI PADA MASA PANDEMI COVID-19 - Egi Destri Nisa Safitri; Heris Hendriana; Riesa Rismawati Siddik (FOKUS (Kajian Bimbingan & Konseling dalam Pendidikan), 2022)
AbstractThis research aims to find out how group guidance services with discussion techniques increase the self-confidence of class XI high school students during the covid-19 pandemic. The method used in this research is descriptive qualitative. The subjects in this study were six students of SMAN 1 Batujajar class XI IPS 2 who had low self-confidence. Data collection techniques using interviews, observation and documentation. Based on the results of research that has been done, there are changes in students before and after the implementation of group guidance services with discussion techniques provided by the guidance and counseling teacher. The conclusion of this study is that group guidance services with effective discussion techniques can help students increase the self-confidence of class XI high school students during the covid-19 pandemic. Keywords: Group guidance, Discussion Techniques, Self-Confidence